Psoriasis, cardiovascular events, cancer risk and alcohol use: evidence‐based recommendations based on systematic review and expert opinion. (11th July 2013) - Richard, M.‐A.; Barnetche, T.; Horreau, C.; Brenaut, E.; Pouplard, C.; Aractingi, S.; Aubin, F.; Cribier, B.; Joly, P.; Jullien, D.; Le Maître, M.; Misery, L.; et al.
Abstract: The relationship between psoriasis, chronic inflammation, cardiovascular risk and risk of cancer has long been debated. In addition, it has been suggested that alcohol consumption may be a risk factor for psoriasis onset and severity. The aim of this study was to develop evidence‐based recommendations on the risk of comorbidities and its management for daily clinical use, focusing on cardiovascular risk, risk of cancer and alcohol use in psoriasis. A scientific committee identified and selected through the Delphi method clinically relevant questions about cardiovascular risk, risk of cancer and alcohol use in psoriasis. To address these questions, a systematic literature search was performed in Medline, Embase and the Cochrane Library databases. Systematic literature reviews including meta‐analysis whenever possible were performed. Subsequently, an Expert board meeting involving 39 dermatologists took place to analyse the evidence and to elaborate recommendations on the selected questions. Recommendations were graded according to the Oxford level of evidence grading system. The degree of agreement of these recommendations was assessed on a 10‐point scale, as well as their potential impact on daily clinical practice. A total of 3242 articles were identified through the systematic literature searches, among which 110 were included in the systematic reviews. Overall, 12 recommendations were elaborated regarding comorbidities management in psoriasis patients. A moderate increased risk of cardiovascular diseases (CVD), mainly myocardial infarction (MI) [meta‐analysis of cohort studies: OR = 1.25 (95% CI 1.03–1.52) and of cross‐sectional studies: OR = 1.57 (95% CI 1.08–2.27)], and coronary artery disease (CAD) [meta‐analysis of cross‐sectional: OR = 1.19 (95% CI 1.14–1.24), of cohort studies: OR = 1.20 (95% CI 1.13–1.27) and of case–control studies: OR = 1.84 (95% CI 1.09‐3.09)] was acknowledged. This increased cardiovascular risk requires appropriate prevention measures. There was a lack of substantial evidence that conventional systemic treatment has any effect on cardiovascular risk although methotrexate might be cardioprotective. An increased risk of solid cancer potentially associated with smoking and alcohol use was identified. The role of systemic treatment on cancer risk could not be assessed thoroughly due to limited long‐term follow‐up data. A higher risk of non‐melanoma skin cancers especially squamous cell carcinoma was shown, mainly due to previous exposure to oral 8‐methoxypsoralen‐ultraviolet‐A (PUVA), ciclosporin and possibly methotrexate. No firm conclusion could be drawn regarding alcohol and psoriasis due to high variability in alcohol usage assessment in studies. Clinical experience suggests higher alcohol consumption among psoriasis patients compared to the general population. The mean expert participants' level of agreement on these recommendations varied from 6.8 to 9.4. These 12 recommendations are evidence based and supported by a panel of expert dermatologists. The next step is now to disseminate these recommendations to dermatologists who did not participate in the Expert board meeting and to assess their opinion about the recommendations.